KAJIAN SIMBOL VISUAL PAWUKON - Mutiara Putri Dhamastuty; Wisnu Adisukma (TEXTURE : Art and Culture Journal, 2018)
Culture is dynamic in the form of humans and vice versa with a value system. One of them is Pawukon, originating from the science of titen and then manifested in the manuscript. In the case of the RadyaPustaka Museum’s collections, inseparable from the history and myths of Watugunung. Interaction and interpretation of analysis are used in historical studies, influences on Javanese people, symbols of Pawukon in the manuscript and the importance of its presence in contemporary society. Mandhasiya and Kuruwelut were chosen as sample of 30 wuku and provided guidance on the existence of the manuscript.Keywords: Kuruwelut, Mandhasiya, Symbol, Wuku